1998
DOI: 10.1159/000013998
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Lead Exposure in Southern Italy

Abstract: We evaluated the blood lead levels in 159 pregnant women and in their healthy newborns at birth. The blood lead levels were higher in mothers as compared with neonates, with a linear correlation between maternal and neonatal levels. The blood lead levels were also higher in neonates as compared with infants aged 6–12 months, and, besides, 2.5% of the newborns had blood lead levels >10 µg/dl, the actual level of concern according to the Center for Disease Control. The study of blood and urinary lead levels duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
2
11
1
Order By: Relevance
“…Our findings that maternal lead levels during pregnancy are strongly related to neonatal lead level are consonant with previously published studies (Amitai et al 1999;Angell and Lavery 1982;Campagna et al 1999;Carbone et al 1998;Chuang et al 2001;Dietrich et al 1987;Graziano et al 1990;Lauwerys et al 1978;McMichael et al 1988;Nashashibi et al 1999;NavarreteEspinosa et al 2000). The correlation in the APILS sample between maternal and neonatal lead levels at parturition is well within the published range from 0.36 (Amitai et al 1999) to 0.92 (Graziano et al 1990).…”
Section: Discussionsupporting
confidence: 94%
“…Our findings that maternal lead levels during pregnancy are strongly related to neonatal lead level are consonant with previously published studies (Amitai et al 1999;Angell and Lavery 1982;Campagna et al 1999;Carbone et al 1998;Chuang et al 2001;Dietrich et al 1987;Graziano et al 1990;Lauwerys et al 1978;McMichael et al 1988;Nashashibi et al 1999;NavarreteEspinosa et al 2000). The correlation in the APILS sample between maternal and neonatal lead levels at parturition is well within the published range from 0.36 (Amitai et al 1999) to 0.92 (Graziano et al 1990).…”
Section: Discussionsupporting
confidence: 94%
“…The cord BLLs found in other countries such as China, Mexico, India, Israel, Pakistan, Tanzania, Turkey, Spain, Belgium and indeed other countries were in general lower than the levels obtained in the present study [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Discussioncontrasting
confidence: 85%
“…A study of 159 motherinfant pairs also found a relatively constant cord/maternal ratio (0.84) over a maternal blood lead range of approximately 1-12 μg/dL (Carbone et al 1998). As noted in the discussion of the distribution of lead in bone, measurements of stable lead isotope ratios in pregnant women and cord blood, as they came into equilibrium with a novel environmental lead isotope signature, indicated that approximately 80% of lead in fetal cord blood appears to derive from maternal bone stores (Gulson et al 2003).…”
Section: Lead In Bonementioning
confidence: 94%
“…The maternal/fetal blood lead concentration ratio, indicated from cord blood lead measurements, is approximately 0.9 (Carbone et al 1998;Goyer 1990;Graziano et al 1990). …”
Section: Lead In Bonementioning
confidence: 99%